Water Quality Assessment in The Occurrence of Acanthaster spp. (Crown-of-Thorns Starfish, CoTS) on Coral Reefs in Menjangan Island, Bali, Indonesia - Pradisty, Novia Arinda; Ampou, Eghbert Elvan; Hanintyo, Rizki (Makara Journal of Science, 2020)
Aquatic stressors are known to cause biological impairment that can result in biodiversity loss in several Marine Protected Areas (MPA), including in Menjangan Island, West Bali National Park. The objectives of this study were to correlate the changes in water quality parameters with the biological effect of Crown-of-Thorns starfish (CoTS) population dynamics and to assess the most applicable parameters for continuous environmental monitoring. Field observations and surveys were conducted three times in 2017, during the wet season, dry season and season transition, in order to assess the effect of seasonal variability. Redundancy Analysis (RDA) was performed to determine the relationship between water quality parameters (temperature, dissolved oxygen, pH, salinity, turbidity, total suspended solids, dissolved inorganic nitrogen and phosphate, and chlorophyll-a) and phytoplankton as the indicator of CoTS larvae food supply. The results demonstrate that salinity, turbidity, and dissolved inorganic nitrogen (DIN) are responsible for the 47.7% of phytoplankton variation, which supports the hypothesis of nutrient enrichment as the trigger of CoTS population increase. CoTS outbreak is predicted to occur during the wet season, in areas with high salinity, moderate turbidity, and high DIN, so the outbreak may be related to a high rainfall rate that deliver a high nutrient loading on this region and thus management actions can be initiated during this specific period.